Pengaruh Kompetensi, Beban Kerja, dan Etika Auditor Terhadap Kualitas Audit - Muhammad Ihsan Randa; Yvonne Augustine Sudibyo (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to examine and analyze the effect of auditor competence, workload, and ethics on audit quality. The sample of the study consists of auditors working at Public Accounting Firms (KAP) in the Jakarta area. The sampling method used is purposive sampling, resulting in 300 respondents. The data used is primary data, obtained through the distribution of questionnaires using Google Forms. The data analysis method employed is multiple linear regression. The results of the study indicate that both auditor competence and ethics have a positive effect on audit quality, while workload has a negative effect on audit quality.